Role of catestatin in development and decompensation of heart failure: a literature review - Yu. V. Meshcheryakov; I. V. Gubareva; E. Yu. Gubareva; A. Yu. Alekseeva (Российский кардиологический журнал, 2021)
The current literature review covers the role of sympathetic nervous system activation (SNS) and the significance of a new biomarker catestatin (CST), which is a chromogranin A-derived peptide, for assessing prognosis of patients with heart failure (HF). This review details the works devoted to CST metabolism and its role in clinical conditions with excessive catecholamine production, including the ability to counterbalance the adverse effects of SNS on cardiovascular system. The paper also presents the central results of studies on HF patients and shows the correlation of the CST level with HF functional class and stage. In addition, particular attention is paid on the possibilities and potential benefits of assessing the CST in addition to conventional management of patients hospitalized due to acute decompensated heart failure.